The Curriculum of Islamic Education in the Classical and Modern Eras and Its Relevance to the Independent Curriculum: A Comparison of the Thoughts of Syed Naquib Al-Attas and Ibn Sahnun - Arifa, Nur; Amrona, Yassir Lana; Aripai, Andi Fatihul Faiz (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
The curriculum of Islamic education has evolved over time, from the classical era to the modern era. In the classical era, there was a scholar who pioneered the Islamic education system, namely Ibn Sahnun. In the modern era, there is Syed Naquib al-Attas, who upholds the Islamization of knowledge. This study aims to discuss whether the content of the curriculum in classical Islamic education designed by Ibn Sahnun and the modern curriculum designed by Al-Attas synergize with each other in terms of the levels of knowledge studied. Furthermore, if we relate it to the Independent Curriculum program currently promoted by the government, is it relevant and compatible with the curriculum designs of these two figures, Ibn Sahnun and Al-Attas? This study employs a descriptive comparative research method and an in-depth analysis of the literature related to these two figures to examine the relevance of their ideas with the Independent Curriculum initiated by the government. The results of this study found that there is compatibility between the classical and modern Islamic education curriculum and the Independent Curriculum in four aspects: first, the aspect of freedom in learning; second, the aspect of attention; third, the aspect of flexibility; and fourth, the aspect of cooperation. This also concludes that there is relevance between the Independent Curriculum and the Islamic education curriculum designed by Al-Attas and Ibn Sahnun regarding compulsory learning related to the Qur'an as the main foundation before understanding other subjects, especially social sciences.Abstrak: Kurikulum pendidikan Islam mengalami perkembangan dari masa ke masa yaitu dari era klasik sampai pada era modern. Pada era klasik, terdapat ulama yang menjadi pelopor sistem pendidikan Islam yaitu Ibnu Sahnun. Kemudian pada era modern terdapat Syed Naquib al-Attas yang menjunjung tinggi islamisasi ilmu pengetahuan. Penelitian ini bertujuan untuk membahas tentang apakah muatan materi yang terdapat dalam kurikulum pendidikan Islam era klasik rancangan Ibnu Sahnun dan kurikulum era modern rancangan Al-Attas memiliki sinergisitas satu sama lain dalam aspek tingkatan keilmuan yang dipelajari? Kemudian jika ditarik dengan program kurikulum merdeka yang sedang digencarkan oleh pemerintah pada saat ini apakah relevan dan memiliki kesesuaian dengan rancangan kurikulum dua tokoh tersebut yaitu Ibnu Sahnun dan Al-Attas? Penelitian ini menggunakan metode penelitian deskriptif komparatif serta analisis yang mendalam terhadap literatur-literatur yang berkaitan dengan kedua tokoh tersebut untuk melihat relevansi gagasan ide kedua tokoh tersebut dengan kurikulum merdeka yang diinisiasi oleh pemerintah. Hasil penelitian ini menemukan bahwa terdapat kesesuaian antara kurikulum pendidikan Islalm era klalsik dan era modern dengan kurikulum merdeka pada empat aspek yaitu: pertama, aspek kebebasan dalam belajar; kedua, aspek memperhatikan; ketiga, aspek fleksibilitas; dan keempat, aspek gotong royong. Hal ini juga memberikan kesimpulan bahwa terdapat relevansi antara kurikululm merdeka dengan kurikulum pendidikan Islam yang dirancang oleh Al-Attas daln Ibnu Sahnun mengenai pembelajaran wajib yang berkenaan dengan Al-Qur’an menjadi dasar utama sebelum memahami materi-materi lain terutama ilmul-ilmul sosial.